Techniques of Utilizing Information in BIM System A comparative Study of International Standards for the UK, USA, Australia and Singapore (Journal of University of Babylon for Engineering Sciences, 2020)
Due to the importance of the Building Information Modeling System (BIM) in the field of architectural design and construction, many countries have published standards and guidelines to organize engineering practice and to overcome its difficulties. The paper investigated the similarities and differences in the methods of managing information in BIM standards of the UK, USA, Australia and Singapore. The aim of the study was to establish a knowledge base for initializing the Iraqi BIM standards. To achieve this aim, the paper put forward a theoretical framework for processing information in the BIM system. The framework identified the methods at two levels. The first level is concerned with the design information, including the techniques of structuring design data, the techniques of storing the database, the techniques of coordinating and classifying building information and the techniques of representing information. The second level, on the other hand, is concerned with the digital techniques supporting the information management in BIM. It includes the techniques of digital collecting and storing information, the techniques of managing and exchanging information, the techniques of digital security, and finally the techniques of integration and interoperability in the digital representation of information. The techniques of utilizing information in BIM were investigated in the descriptions of the standards and guidelines of the four countries to determine their similarities and differences.The comparative analysis findings revealed similarities in the techniques of digital storing, collecting and organizing information, in addition to the techniques of digital security and integration and interoperability of information. In this case, the shared techniques can be adopted in the Iraqi standards. The differences can be found in the techniques of structuring the design data, storing the database in the national library, and coordinating, classifying and representing the design information. They reflect the specificity of each country in the implementation of BIM. Therefore, these techniques Requires special preparation for the Iraqi standards of BIM.